Blockage of Autophagic Flux and Induction of Mitochondria Fragmentation by Paroxetine Hydrochloride in Lung Cancer Cells Promotes Apoptosis via the ROS-MAPK Pathway - Wang, Kun; Gong, Qing; Zhan, Yujuan; Chen, Bonan; Yin, Ting; Lu, Yuhua; Zhang, Yilin; Wang, Huiqi; Ke, Junzi; Du, Biaoyan; Liu, Xiaodong; Xiao, Jianyong (Frontiers in Cell and Developmental Biology, 2020)
Cancer cells are characterized by malignant proliferation and aberrant metabolism and are thereby liable to the depletion of nutrients and accumulation of metabolic waste. To maintain cellular homeostasis, cancer cells are prone to upregulating the canonical autophagy pathway. Here, we identified paroxetine hydrochloride (Paxil) as a late autophagy inhibitor and investigated its killing effect on lung cancer cells and with a xenograft mouse model in vivo. Upregulated LC3-II and p62 expression indicated that Paxil inhibited autophagy. Acid-sensitive dyes (e.g., Lysotracker and AO staining) indicated reduced lysosomal acidity following Paxil treatment; consequently, the maturation of the pH-dependent hydroxylases (e.g., cathepsin B and D) substantially declined. Paxil also induced the fragmentation of mitochondria and further intensified ROS overproduction. Since the autophagy pathway was blocked, ROS rapidly accumulated, which activated JNK and p38 kinase. Such activity promoted the localization of Bax, which led to increased mitochondrial outer membrane permeability. The release of Cytochrome c with the loss the membrane potential triggered a caspase cascade, ultimately leading to apoptosis. In contrast, the clearance of ROS by its scavenger, NAC, rescued Paxil-induced apoptosis accompanied by reduced p38 and JNK activation. Thus, Paxil blocked the autophagic flux and induced the mitochondria-dependent apoptosis via the ROS-MAPK pathway.